Pluralisme Agama Perspektif Abdul Karim Soroush: Kajian Teoritis dan Filosofis - Faza 'Ainun Najah; Hakam Al-Ma’mun (Fakultas Syariah IAIN Laa Roiba Bogor, 2023)
Pluralism, in the context of religion, on the one hand is an established term that is understood as a necessity that cannot be denied, but on the other hand, pluralism seems full of misunderstandings because it assumes that all beliefs are true. This debate will not seem to meet a common ground because human thoughts continue to develop and clash with each other. A modern reformist Islamic figure, Abdulkarim Soroush, comes up with arguments that support the spirit of pluralism. His thoughts are interesting because they often contradict other Muslim figures in Iran. This study aims to explore deeply the values ​​of religious pluralism from a figure who is labeled a